Kinematic Profile of Ashwa Sanchalana Asana: Development of a Kinematic Profile for Ashwa Sanchalana Asana (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The present study was initiated with the aim of developing a kinematic profile ofAshwasanchalana Asana on the basis of selected kinematic variables. 50 Subjects of Gwalior district tookpart in this study voluntarily. A written consent form was signed by them to be the part of research work.They all were asked to perform Ashwasanchalana Asana thrice their performance was filmed usingAkaso V50 pro action camera at 60 fps. 6 Angular kinematic variables (Ankle, knee, hip, shoulder, elbow,wrist) with 1 linear kinematic variable (Height of center of gravity) were selected for the purpose of thestudy. As a result of the study a profile chart was developed using selected kinematic variables